(untitled) (Zien Journal of Social Sciences and Humanities, 2025)
This article explores the artistic representation of womanhood and morality in Theodore Dreiser’s novel Jennie Gerhardt (1911). Through the lens of literary realism and naturalism, Dreiser portrays the female protagonist not merely as a victim of social circumstances but as a complex individual shaped by socioeconomic limitations, moral dilemmas, and emotional resilience. The article examines how Dreiser’s narrative choices, character construction, and thematic elements reflect his critique of societal norms and gender expectations. The study contributes to a deeper understanding of early 20th-century American literature’s engagement with issues of female identity, morality, and artistic forma